ANALISIS EFEKTIVITAS IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM PENGELOLAAN PROGRAM HARIAN DI SD NEGERI 2 SESETAN - Ida Bagus Gede Surya Abadi; Chindytia; Ni Luh Rai Mita Rachma Putri; Ni Komang Sri Mulianingsih; Ni Luh Putu Mila Rachma Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effectiveness of School-Based Management (SBM) in managing daily school programs at the primary level, addressing a gap in prior studies that predominantly emphasize structural and administrative dimensions rather than practice-based implementation. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving the principal and teachers, and analyzed using an interactive model with triangulation to ensure validity. The findings indicate that SBM effectiveness is demonstrated through the operational integration of autonomy, participation, and accountability into daily school practices. The novelty of this study lies in positioning daily programs as a micro-level governance mechanism through which SBM is enacted and sustained. Programs such as PACAR CINA, PALING GAMES, DORAMI, MELALI, and JUST SEGAR function as strategic instruments for embedding character education and strengthening school culture. Collaborative leadership and participatory decision-making serve as key enabling factors, while infrastructural constraints and limited development of contextual pedagogy remain persistent challenges. By shifting the analytical focus from structural compliance to situated practice, this study contributes to the refinement of SBM discourse and highlights the importance of continuous, context-sensitive improvement to enhance the quality of primary education.